口内法下顎頭切除術を適用した陳旧性両側顎関節脱臼の1例 - 根岸, 明秀; 柴崎, 麻衣子 (日本口腔外科学会雑誌, 2017)
Opportunities to treat elderly patients with temporomandibular joint (TMJ) dislocation complicated by systemic diseases or dementia have been increasing in recent years. Reduction is often particularly difficult in patients with long-standing TMJ dislocation caused by the soft tissue filling the mandibular fossa.　The treatment procedure for long-standing TMJ dislocation begins with a noninvasive therapy such as closed reduction or traction therapy with leverage. If noninvasive therapy is unsuccessful, invasive therapy involving open reduction would be performed, and if reduction fails, the mandibular condyle may be resected as a last resort. Condylectomy has often been reported to be performed using an extraoral approach via a preauricular incision. However, in TMJ dislocation, the mandibular condyle is situated further forward, allowing the mouth to be opened sufficiently. This enables resection of the mandibular condyle using an intraoral approach based on sagittal split ramus osteotomy.　We performed an intraoral condylectomy to treat long-standing bilateral TMJ dislocation in an elderly patient with cerebrovascular disorder because noninvasive reduction such as closed reduction and traction therapy with leverage was ineffective. After surgery, the patient was able to chew and ingest food orally. Intraoral condylectomy is a potential therapeutic option in cases of long-standing TMJ dislocation with maintained occlusal support that cannot be reduced by noninvasive therapy.